Fintech Innovation and Hedonism Lifestyle on Student Financial Sustainability with Financial Intelligence as an Intervening Variable - Prastyorini, Juli (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This research aims to test and analyze the direct and indirect influence of fintech innovation and a hedonistic lifestyle on student financial sustainability through financial intelligence on STIAMAK students in Surabaya. The variables used in this research are fintech innovation and hedonism lifestyle as independent variables, financial intelligence as an intervening variable and student financial sustainability as the dependent variable. This type of research is explanatory research. The number of samples used in the research was 72 students at STIAMAK University Surabaya with the sampling technique used was purposive random sampling. The data analysis technique used is path analysis using SmartPLS. The results show that fintech innovation, either directly or indirectly, has no influence on student financial sustainability, the hedonistic lifestyle, both directly and indirectly, has an influence on the financial sustainability of STIAMAK students in Surabaya.